298 Multidisciplinary maximum effort cyto-reductive surgery (MES) for advanced ovarian cancer in leicester: outcomes. (18th September 2019) - Ismail, A; Ofinran, O; Davies, Q; Moss, E; Bharathan, R; Boyle, K; Thomas, M; Malde, D; Bhardwaj, N; Camacho, E; Chattopadhyay, S
Abstract : Objectives: It is recognised that adequate debulking in ovarian cancer surgeries does improve the survival rate; In Leicester, we have implemented a structured multidisciplinary surgical approach to offer Maximum effort surgery (MES) to our patients with advanced ovarian cancer. The surgical team includes gynae-oncologists, hepatobiliary/colorectal surgeons, and anaesthetic team. This approach has helped us develop effective skills in extensive complex abdominal surgeries, and optimising the intraoperative decision making, hence improving the outcomes. Methods: A retrospective evaluation of prospectively collected data was performed to assess the surgical outcomes of all consecutive patients who underwent ultra-radical surgery for advanced ovarian cancer, from January 2016 to February 2019. Results: 39 consecutive women had MES. Median age was 65(range 27–86). 19(49%) had PDS and 18(46%) had IDS while 2(5%) had secondary cytoreduction. The majority of the patients were stage IIIC or above (92%) and most were high grade serous histology (85%). The median surgical duration was 297 minutes. Complete cytoreduction with no gross residual disease (GRD) was achieved in 87% of the patients, 8% had GRD <1cm and only 5% had suboptimal cytoreduction. Median blood loss was 800mls. Median length of hospital stay was 9 days. One patient died in the first 28 days post-surgery. The postoperative complications are presented in table 1 using the Clavien-Dindo classification. Conclusions: Our data favours a multidisciplinary structured MES service for advanced ovarian cancer and this could be a more effective approach than a unidisciplinary approach. It minimises the morbidity, enables the development interdisciplinary surgical skills and improves the quality of surgery.